2023
DOI: 10.3390/jpm13050840
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Influencers and Associated Factors That Shape Jaw Movement and Growth in Temporomandibular Joint Disorder Management: A Systematic Review of Clinical and Radiographic Evidence

Abstract: Objective. To investigate the influence of endogenous and exogenous neuroendocrine analogues on the range and motion of jaw movement, mandibular growth, and factors affecting condylar guidance in patients with temporomandibular joint disorders using clinical assessment and radiographic imaging. Material and Methods. Eligible articles were extracted from eleven databases in early 2023 and screened following PRISMA protocols. Certainty of evidence and potential biases were assessed using the GRADE approach. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Predisposing medical conditions and subsequently prescribed medication can alter the physiology of jaw kinematics [2]. Estrogen and progesterone supplements, frequently prescribed to female participants, have been demonstrated in several instances to alter jaw kinematics [2]. Vitamin D deficiency, contributing to 14.97% of the incidences of jaw clicking in the current study, affects one third of the Australian population [30].…”
Section: Medical Conditions and Jaw Clickingmentioning
confidence: 71%
See 2 more Smart Citations
“…Predisposing medical conditions and subsequently prescribed medication can alter the physiology of jaw kinematics [2]. Estrogen and progesterone supplements, frequently prescribed to female participants, have been demonstrated in several instances to alter jaw kinematics [2]. Vitamin D deficiency, contributing to 14.97% of the incidences of jaw clicking in the current study, affects one third of the Australian population [30].…”
Section: Medical Conditions and Jaw Clickingmentioning
confidence: 71%
“…Predisposing medical conditions and subsequently prescribed medication can alter the physiology of jaw kinematics [2]. Estrogen and progesterone supplements, frequently prescribed to female participants, have been demonstrated in several instances to alter jaw kinematics [2].…”
Section: Medical Conditions and Jaw Clickingmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory disorders such as osteoarthritis can restrict bony translation as well as generate resistive muscle tension [ 16 ]. Historically, drastic changes in jaw movement have been reportedly caused by a shallow compensating curve, shortened dental arch, trauma, TMD and severe changes to occlusal facets, condylar guidance and certain neuroendocrine conditions [ 17 , 18 ]. The current study found participant 2 to have shorter quantitative maximum mouth opening cycles, leading to more frequent movement cycles per 5 seconds, consistent with their clinical presentations while normal mouth opening cycles were seemingly unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 demonstrates the steps of clinical data collection for the study and are explained in the subsections below. Prior to conducting the current research, systematic reviews were conducted on the most common sources of biases arising from human and device-dependent factors in jaw tracking and AI-based decisions concerning the temporomandibular joint complex 2 , 5 , 8 , 9 . The current research evaluations build upon a systematic series of prior investigations, documented in the following subsections.…”
Section: Methodsmentioning
confidence: 99%